Assessment of wash load transport in the Araguaia River (Aruanã Gauge Station), central Brazil (Latin American Journal of Sedimentology and Basin Analysis, 2021)
With an area close to 377,000 km2 and a mean annual discharge of ~ 6,420 m3 s-1 the Araguaia River is the main river draining the central highlands of Brazil. The Araguaia Rivers is a particularly sandy anabranching system that has been suffering geomorphologic and sedimentary changes because of the effect of high rates of deforestation during the last decades. Little is known, however, on the amount of wash load transport. We will present the first relatively systematic results on wash load transport for the Araguaia River at the Aruanã gauge station. The drainage area at Aruanã is 77,000 km2 and the mean annual discharge is ~1,200 m3 s-1. A total of 140 samples from 20 field surveys were analyzed and the wash load transport was estimated. We calculated that from 2001-2007 the average annual transport oscillated between 8 Mt yr-1 and 6 Mt yr-1. An interesting aspect that makes the Araguaia unique when compared to other large alluvial rivers of Brazil is the relation between sandy load and wash load. The Araguaia at Aruanã carries up to ~57% of the total sediment load as sandy load. We can now conclude that wash load just represents near 43 to 49% of the total sediment load in this system. Our results demonstrate that previous works overestimated the total wash load transported by the Araguaia. Taking into account that these are the first systematic results on wash load transport in the Araguaia, proposed human interventions in this system affecting sediment flows such as dams can be extremely harmful for the fluvial system. A more systematic analysis of sediment transport and an integrated and multidisciplinary plan of basin management must be done so that the detrimental effects of these human interventions will be understood.
Keywords: Wash load; Deforestation; Sediment transport; Araguaia; Central Brazil